Gamma-Ray Burst Science in 2030 - Moretti, Elena; Longo, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains a series of articles and reviews that illustrate the state-of-the-art knowledge about Gamma Ray Bursts and provide deep insights on the challenges that will be faced in GRB physics in the next decade.